Differences of Ki-67 Expression in Basal Cell Carcinoma Low-Risk and High-Risk Subtypes associated with Age, Gender, Location of the Lesion and Histologic features - Mochamad Sonny Yanuar Akbar; Siti Amarwati; Udadi Sadhana; Ika Pawitra Miranti; Meira Dewi Kusuma Astuti (Universitas Hang Tuah, 2023)
Background: An increase in the number of BCC worldwide has also resulted in an increase in the rate of disability, recurrence and increased treatment costs, so additional examinations are needed to support existing standard histological examinations so as to produce a precise and accurate diagnosis. No accurate data on Ki-67 expression in BCC subtypes have been published yet Objective: To evaluate differences of Ki-67 expression in low-risk and high-risk basal cell carcinoma subtypes associated with age, sex, lesion location and histologik features Methods: In 2017-2020 there were 39 samples of paraffin blocks diagnosed as low-risk and high-risk BCC subtypes at Dr. Kariadi Hospital. Consecutive sampling method was used, namely 29 samples of low subtype and 10 samples of high subtype of BCC. Results: All sample are positive for Ki-67 in low risk BCC and high risk subtypes, with differences between subtypes (p = 0.084) indicating no significant difference in Ki-67 expression on both BCC subtypes. Conclusion: Expression of Ki-67 low risk subtype at age > 60 years female gender and high risk subtype age > 60 years male gender.